Emergence and dissemination of monkeypox, an intimidating global public health problem - Hasan Ejaz; Kashaf Junaid; Sonia Younas; Abualgasim E. Abdalla; Syed Nasir Abbas Bukhari; Khalid O.A. Abosalif; Naveed Ahmad; Zeeshan Ahmed; Manhal Ahmed Hamza; Naeem Anwar (Elsevier, 2022)
The monkeypox virus (MPXV) is the cause of a zoonotic infection similar to smallpox. Although it is endemic to Africa, it has recently begun to circulate in other parts of the world. In July 2022, the World Health Organization declared monkeypox an international public health emergency. This review aims to provide an overview of this neglected zoonotic pathogen. MPXV circulates as two distinct clades, the Central African and West African, with case fatality rates of 10.6% and 3.6%, respectively. The risk of infection is greater for those who work with animals or infected individuals. The virus' entry into the human body provokes both natural and acquired immunity. Although natural killer cells, CD4 + T cells, and CD8 + T cells play an essential role in eradicating MPXV, there is still a gap in the understanding of the host immune response to the virus. Currently, there are no specific therapeutic guidelines for treating monkeypox; however, some antiviral drugs such as tecovirimat and cidofovir may help to abate the severity of the disease. The use of nonpharmaceutical interventions and immunization can reduce the risk of infection. Increased surveillance and identification of monkeypox cases are crucial to understand the constantly shifting epidemiology of this resurging and intimidating disease. The present review provides a detailed perspective on the emergence and circulation of MPXV in human populations, infection risks, human immune response, disease diagnosis and prevention strategies, and future implications, and highlights the importance of the research community engaging more with this disease for an effective global response.